Clinical and Pathologic Predictors of Clinical Outcome of Malignant Pleural Mesothelioma. Issue 2 (March 2016) - Berardi, Rossana; Fiordoliva, Ilaria; De Lisa, Mariagrazia; Ballatore, Zelmira; Caramanti, Miriam; Morgese, Francesca; Savini, Agnese; Rinaldi, Silvia; Torniai, Mariangela; Tiberi, Michela; Ferrini, Consuelo; Onofri, Azzurra; et al.
Aims and background: Although worldwide use of asbestos has decreased, the incidence of malignant pleural mesothelioma (MPM) is expected to increase over the next few decades. A number of scoring systems has been proposed to assess clinicopathologic features and to predict the prognosis. We assessed the relationship between patients' features and disease evolution in order to choose the best treatment able to prolong overall survival (OS) and progression-free survival (PFS). Methods: We retrospectively analyzed patients with locally advanced or metastatic MPM, treated at the Department of Medical Oncology, Università Politecnica Marche, Italy, from January 2003 to September 2013. Data on age, sex, smoking history, asbestos exposure, performance status, tumor stage, histology, type of treatment, and routine laboratory tests including complete blood count panel, date of death, or censored status were collected. The OS and PFS were estimated using Kaplan-Meier method and Cox analysis was performed to analyze the prognostic relevance of clinical parameters. Results: We enrolled a total of 62 patients. Univariate analysis showed that histologic type, performance status, response to first-line therapy, pretreatment hemoglobin levels, and plasmatic Ca125 were significant prognostic factors. Conversely, no significant correlation was found between age, sex, smoking history, reported exposure to asbestos, stages at diagnosis, treatments, and OS and PFS. Conclusions: Our results showed that anemia and increased Ca125 might be considered negative prognostic parameters in MPM patients and confirmed the prognostic role of histotype, performance status, and response to first-line chemotherapy.